An Epidemiological Study on Infestation Rate of Ticks in Ruminants of Sargodha Division Pakistan - Niazi, Mehwish; Ahmed, Zunnorain; Ahmed, Naseer; Hafeez, Sadia; Fatima, Eman; Farooq, Usama; Yousaf, Muqaddas; Khan, Fatima; Cheema, Imtiaz Ahmed; Abdur Rehman (Indus Journal of Bioscience Research, 2025)
This study investigated tick infestation rates and their distribution on various body parts of ruminants in Sargodha Division, comprising four districts. Samples were collected from 10 farms per district between February and June 2021. Of the 1,067 ruminants (cows, buffaloes, goats, and sheep) observed, 348 (32.10%) were infested. The highest infestation rate was recorded in Mianwali (54.44%), followed by Sargodha (28.92%), Bhakkar (25.69%), and Khushab (24.71%). Among species, cows were the most infested (41.45%), followed by buffaloes (33.73%), sheep (27.38%), and goats (16.41%). Female cows (45.10%) were more infested than males (31%), while male buffaloes (59.37%) showed higher infestation than females (33.58%). Male sheep (34.44%) and goats (29.41%) were also more infested than their female counterparts. In female cows, ticks were predominantly found on the tail (50.42%) and udder (36.75%), while in female buffaloes, the udder (79.77%) and tail (70.78%) were most infested. Male cows and buffaloes had the highest tick distribution on the testicles and dewlap. Ticks were predominantly found in the ears of all infested goats and sheep, regardless of sex. This study highlights that species, sex, and body part preferences significantly influence tick infestation rates. As the first report on tick infestation in Sargodha Division, it provides valuable insights for controlling ticks and related diseases in ruminants, paving the way for future research and management strategies.